The kinetics of Mangifera indica L. peel waste as sorbent of lead and cadmium in water - Ng, Vincent Antonio (Santos)
Mango peel waste was tested for its ability to adsorb lead and cadmium, two of the most toxic heavy metals in water. The study identified the optimum conditions for the sorption of lead and cadmium, thus kinetic parameters such as initial metal concentration, pH, time of contact and amount of sorbent was varied and tested for sorption efficiency. Analysis using atomic adsorption spectroscopy revealed that mango peel waste can effectively remove lead by as much as 93% and cadmium by as much as 81%. The process of adsorption is instantaneous for both lead and cadmium., The efficiency of lead and cadmium removal is directly proportional to the amount of mango peel waste added. Statistical analysis using multi-factorial analysis of variance showed that at 95% confidence level, the groups within each kinetic parameters are significantly different from each other and that interactions are present between the kinetic parameters. The mechanics of sorption of lead and cadmium towards mango peel waste fit both the Langmuir and Freundlich isotherm models.